The construction of marketing measures: the case of viewability - Cluley, Robert (Sage, 2018)
This study seeks to develop a critical understanding of marketing measures. Marketing measures inform a variety of marketing practices and have been subject to ethical, discursive and epistemological critique. Informed by a range of theoretical work, this study sheds light on the construction of a key marketing measure in digital advertising: viewability. It shows how a range of competing interests can be mobilized and aligned; how an object of interest can be stabilized; and how standards for measurement can be reconciled. Across this account, we can see how issues of accuracy, ideology and ethics are bracketed off as participants agree on which things matter and which things count.